THE POSSIBILITY OF NEUTRALIZING WHITE PHOSPHORUS USING MICROBIAL CULTURES - A. Z. Mindubaev,; E. V. Babynin,; A. D. Voloshina,; K.A. Saparmyradov,; Y. A. Akosah,; E. K. Badeeva,; S. T. Minzanov,; L. G. Mironova, (Academic Scientific Journal of Chemistry, 2019)
The growth of microorganisms of various taxonomic groups (fungi, streptomyces and bacteria) was observed for the first time in culture media containing white phosphorus P4 as the source of phosphorus. This is the first known example of the incorporation of white phosphorus into the biospheric circulation of the phosphorus element. The highest concentration applied in this study exceeds the Threshold Limit Value (TLV) of white phosphorus in wastewater by 5000 times, and in drinking water by up to 100,000,000 times! The growth selection of cultures resistant to P4 was carried out for the first time. We identified the microorganisms, growing on white phosphorus, as new strains of Aspergillus niger and Streptomyces sampsonii. The number A. niger AM1 and S. sampsonii A8 were assigned to them, respectively. Strains of the A. niger isolates were shown to better adapt to P4 than the bacteria.